FADN data to support policymaking: The potential of an additional survey - Federica Cisilino; Greta Zilli; Gabriele Zanuttig (Economia Agro-Alimentare, 2021)
This paper aims to highlight the potential of a FADN additional survey when payment for organic farming is to be calculated in the rural development decision-making process. In fact, the number of organic farms included in the FADN is often too low to provide consistent results. The analysis is based on a direct survey conducted on a larger number of farms than those included in the FADN continuous sample, considering the organic grape-growing farms. The estimate of the appropriate support payments (amount per hectare) is based on the gross margin methodology which allows additional costs and income foregone at micro-level to be highlighted. The method uses the partial balance sheet of a single crop processing to compare costs and revenues of organic and conventional grape-growing farms and considering both certification and transaction costs.